Non-Markovian Queueing System, Mx/G/1 with Server Breakdown and Repair Times - Agrawal3, Deepak Gupta1*, Anjana Solanki2, K.M. (Recent Research in Science and Technology, 2011)
This paper deals with the steady state behavior of an MX/G/1 queue with breakdown. It assumed that customers arrive to the system in batches of variable size, but serve one by one. The main new assumption in this paper is that the repair process does not start immediately after a breakdown and there is a delay time waiting for repairs to start. We obtain steady state results in explicit and closed form in terms of the probability generating functions for the number of customers in the queue, the average waiting time in the queue.